Прогноз землетрусів у рухомих поясах Землі за даними досліджень пластових тисків у природних резервуарах - Орлов, О.О.; Євдощук, М.І. (Видавничий дім "Академперіодика" НАН України, 2007)
In mobile seismo-dangerous layers of the Earth, the anomalously high bedded pressures in isolated collectors are considered as a consequence of the tectonic tensions manifestation in mountain rocks. It is possible to quantitatively determine the increase of tectonic tensions Δ σx,y and to make conclusions about approaching the seismo-dangerous situation by observing the increase of surplus layer pressures Δ P in the isolated natural reservoirs by solving the inverse task.